Return to sports and clinical outcomes in patients treated for peroneal tendon dislocation: a systematic review - van Dijk, Pim A. D. (Knee Surg Sports Traumatol Arthrosc, 2015)
PURPOSE: The aim of this study was to determine the outcome following different surgical treatment techniques in the treatment of peroneal tendon dislocation and to establish whether return to sports was achieved universally following the procedures. METHODS: A systematic review and best-evidence synthesis was performed. PubMed and EMBASE were searched for eligible studies. The last search was done in March 2015. Quality assessment of pooled data was performed using a modified Macleod scale and a best-evidence synthesis was performed. In total, 14 studies were included. RESULTS: Surgical treatment provides improvement in the post-operative AOFAS score (p < 0.0001) and high satisfaction rates. The redislocation rate is less than 1.5 % at long-term follow-up. Patients treated with both groove deepening and SPR repair have higher rates of return to sports than patients treated with SPR repair alone (p = 0.022). CONCLUSIONS: Surgical treatment of peroneal tendon dislocation provides good outcomes, high satisfaction and a quick return to sports. Rates in return to sports are significantly higher in patients treated with both groove deepening and SPR repair. To optimize treatment, the surgical management should involve increasing the superior peroneal tunnel volume by groove deepening and stabilizing the tendons by SPR repair. LEVEL OF EVIDENCE: Level IV, systematic review of level IV studies.